Myeloid Mineralocorticoid Receptor Transcriptionally Regulates P-Selectin Glycoprotein Ligand-1 and Promotes Monocyte Trafficking and Atherosclerosis. Issue 11 (7th October 2021) - Man, Joshua J.; Lu, Qing; Moss, M. Elizabeth; Carvajal, Brigett; Baur, Wendy; Garza, Amanda E.; Freeman, Roy; Anastasiou, Marina; Ngwenyama, Njabulo; Adler, Gail K.; Alcaide, Pilar; Jaffe, Iris Z.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: MR (mineralocorticoid receptor) activation associates with increased risk of cardiovascular ischemia while MR inhibition reduces cardiovascular-related mortality and plaque inflammation in mouse atherosclerosis. MR in myeloid cells (My-MR) promotes inflammatory cell infiltration into injured tissues and atherosclerotic plaque inflammation by unclear mechanisms. Here, we examined the role of My-MR in leukocyte trafficking and the impact of sex. Approach and Results: We confirm in vivo that My-MR deletion (My-MR-KO) in ApoE-KO mice decreased plaque size. Flow cytometry revealed fewer plaque macrophages with My-MR-KO. By intravital microscopy, My-MR-KO significantly attenuated monocyte slow-rolling and adhesion to mesenteric vessels and decreased peritoneal infiltration of myeloid cells in response to inflammatory stimuli in male but not female mice. My-MR-KO mice had significantly less PSGL1 (P-selectin glycoprotein ligand 1) mRNA in peritoneal macrophages and surface PSGL1 protein on circulating monocytes in males. In vitro, MR activation with aldosterone significantly increased PSGL1 mRNA only in monocytes from MR-intact males. Similarly, aldosterone induced, and MR antagonist spironolactone inhibited, PSGL1 expression in human U937 monocytes. Mechanistically, aldosterone stimulated MR binding to a predicted MR response element in intron-1 of the PSGL1 gene by ChIP-qPCR. Reporter assays demonstrated that this PSGL1 MR response element is necessary and sufficient for aldosterone-activated, MR-dependent transcriptional activity. Conclusions: These data identify PSGL1 as a My-MR target gene that drives leukocyte trafficking to enhance atherosclerotic plaque inflammation. These novel and sexually dimorphic findings provide insight into increased ischemia risk with MR activation, cardiovascular protection in women, and the role of MR in atherosclerosis and tissue inflammation.